Effects of two immunosuppression regimens on T-lymphocyte subsets in elderly kidney transplant recipients - Freitas, Geraldo Rubens R.; Fernandes, Maria da Luz; Agena, Fabiana; Lemos, Francine B. C.; Paula, Flavio J. de; Coelho, Verônica; David-Neto, Elias; Galante, Nelson Z. (Frontiers in Immunology, 2024)
Background Despite the growing number of elderly kidney transplant (Ktx) recipients, few studies have examined the effects of immunosuppression on their lymphocyte profiles. Methods We evaluated the early conversion from mycophenolate sodium (MPS) to everolimus (EVL) after rabbit antithymocyte globulin (rATG) 2 mg/kg induction in elderly kidney recipients. Three groups of KTx patients were compared: (a) Young (n=20, 36 ± 7 y) receiving standard immunosuppression (Group A1) (prednisone, tacrolimus, and MPS), (b) Elderly (n=35, 65 ± 3 y) receiving standard immunosuppression (Group B1), and (c) Elderly (n=16, 65 ± 3 y) with early (mean 30 d) conversion from MPS to EVL (Group B2). Naive, memory, and regulatory peripheral blood TCD4+ lymphocytes were quantified at 0, 30, and 365 d. Results Results are reported as [mean(p25–p75)]. Young recipients had higher lymphocyte counts at baseline [2,100(1,630–2,400) vs. 1,310 (1,000–1,600)/mm3, p<0.0001] maintained higher counts within 365 d [1,850(1,590–2,120) vs. 1,130(460–1,325)/mm3, p=0.018 and vs. 1,410(805–1,895)/mm3, p=0.268]. Elderly recipients showed a decrease in lymphocytes within 30 d [1,310(1,000–1,600) vs. 910(700–1,198)/mm3, p=0.0012] with recovery within 365 d. The same pattern was observed in total lymphocytes and TCD4+ counts. Rabbit antithymocyte globulin induced a reduction in central memory T-cell percentages at 30 d in both young recipients [6.2(3.77–10.8) vs. 5.32(2.49–7.28)% of CD4+, p=0.036] and in elderly recipients [8.17(5.28–12.88) vs. 6.74(4.36–11)% of CD4+, p=0.05] on standard immunosuppression, returning to baseline at 365 d in elderly recipients but not in young recipients. Regulatory T CD39+ cells (Treg) percentages decreased at 30 d in elderly recipients [2.1(1.23–3.51) vs. 1.69(0.8–2.66)% of CD4+, p=0.0028] and in young recipients [1.29(0.45–1.85) vs. 0.84(0.18–1.82)% of CD4+, p=0.0038], returning to baseline at 365 d in elderly recipients [2.1(1.23–3.51) vs. 2.042(0.88–2.42)% of CD4+], but not in young recipients [1.29(0.45–1.85) vs. 0.86(0.7–1.34) % of CD4+]. The elderly everolimus conversion group did not show significant changes in cell profile over time or compared to elderly recipients with standard immunosuppression. Conclusion Aging favored the maintenance of Treg during the late transplantation period despite ongoing immunosuppression. Lymphocyte depletion due to rATG was more prominent in elderly recipients and affected memory subsets with a temporary reduction in central memory T cells. However, conversion to everolimus did not impact Treg profile. Reducing the dose of rATG in elderly recipients seems necessary for the expected lymphocyte changes with EVL to occur. Clinical trial registration nEverOld Trial, identifier NTC01631058.